Toxoplasma gondii in sheep: Serological occurrence at slaughterhouse level in Italy and environmental risk factors - Condoleo, Roberto; Rombolà, Pasquale; Palumbo, Roberta; Santori, Davide; Serra, Salvatore; Tonon, Sara; Bosco, Antonio; Sezzi, Erminia (Frontiers in Veterinary Science, 2023)
Toxoplasmosis is a parasitic disease of a wide range of species, including humans, and can be responsible for important clinical manifestations such as abortion and neurological signs. Sheep show a remarkable susceptibility to its causative agent, Toxoplasma gondii, and zoonotic transmission may occur in case of consumption of undercooked meat derived from infected animals. Toxoplasma gondii seroprevalence in sheep can significantly vary on geographical basis as shown by numerous surveys conducted worldwide. To investigate environmental and climate conditions which may affect the likelihood of ovine infection, 405 serum samples, from selected sheep raised in 91 farms, were collected from two abattoirs, each abattoir receiving animals from two regions (1/Tuscany-Latium and 2/Campania-Basilicata). The seroprevalence of infection in all examined animals was 53.8%. Young animals (n = 165) had a lower likelihood of being positive comparing to the adults (OR = 0.21) and seropositive rate of animals slaughtered in abattoir 2 were significantly higher than those of abattoir 1 (60.5% vs 43.2%, p < 0.01). The significant bioclimatic variables (p < 0.05) associated with the presence of T. gondii antibodies were related to areas with lower range of temperature and higher precipitation. In conclusions, this approach expands the interpretation of serological data, with the inclusion of environmental and climatic variables, as possible risk factors in the spread of toxoplasmosis in the study area. These findings provide novel insights to support public health measures, such as risk-based control plan, and contributes to a “One Health” approach, taking into account the environmental and climatic perspective.